1991
DOI: 10.1093/intimm/3.8.743
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of CD16CD56+ natural killer cells with high affinity interleukin 2 receptors in human early pregnancy decidua

Abstract: Most human peripheral blood natural killer (NK) cells express the phenotype CD16+CD56+. However, a very minor subset of NK cells express CD16-CD56+, and these NK cells bear both interleukin 2 receptor (IL-2R)alpha (p55) and IL-2R beta (p75) (high affinity IL-2 receptors). In this report, we demonstrate that in human early pregnancy decidua--an interface between maternal immunocompetent cells and fetus (placenta)--abundant (approximately 83%) CD16-CD56+ NK cells with high affinity IL-2 receptors were present, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 0 publications
5
39
0
Order By: Relevance
“…À NK cells represent the vast majority of immune cells in the early pregnancy decidua [Moffett-King 2002;Nishikawa et al 1991]. A recent study showed that accumulation of CD56 bright , granulysin-positive uNK cells in the decidua basalis was linked to pregnancy loss in humans [Nakashima et al 2008].…”
Section: Uterine Natural Killer Cellsmentioning
confidence: 99%
“…À NK cells represent the vast majority of immune cells in the early pregnancy decidua [Moffett-King 2002;Nishikawa et al 1991]. A recent study showed that accumulation of CD56 bright , granulysin-positive uNK cells in the decidua basalis was linked to pregnancy loss in humans [Nakashima et al 2008].…”
Section: Uterine Natural Killer Cellsmentioning
confidence: 99%
“…140 Similar NK-like cells have also been identified in the human uterus and have the phenotype CD56 bright CD16 Ϫ . 141,142 These NK cells are located at the maternal/ fetal junction and are thought to play a role in regulating implantation and trophoblast invasion, but the factors governing their localization or differentiation are unclear. 143 Uterine NK cells express IL-15R components, and IL-15 increases the expression of NK cytolytic mediators (perforin and granzymes) in pregnant uterine tissue explanted in vitro, 144 as well as in primary mouse uterine NK cells.…”
mentioning
confidence: 99%
“…4,5 NK cells interact with target cells by a series of inhibitory and activating NK cell receptors constitutively expressed by uNK cells. Furthermore, CD16…”
Section: Nk Cells Were Cocultured With Evt Cells (Htr-mentioning
confidence: 99%
“…The decidual mononuclear cells (leukocytes) were purified by the standard Ficoll-Hypaque (Nycomed Pharma, Oslo, Norway) density gradient centrifugation after homogenization and filtration through a 32-mm nylon mesh as previously reported. 4 The cells were then suspended in RPMI 1640 medium supplemented with 10% fetal calf serum, 100 U/ml penicillin, and 100 g/ml streptomycin, and incubated for 2 hours at 37°C in an atmosphere of 5% CO 2 to allow adherent cells to attach to the plastic. The supernatant containing decidual lymphocytes was then collected and the cells were used for analysis.…”
Section: Isolation Of Decidual Lymphocytesmentioning
confidence: 99%